Comparative Efficacy of 5% Dapsone Gel Vs 1% Clindamycin Gel in the Treatment of Mild to Moderate Acne Vulgaris - Abid, Rabia; Saleem, Summaya; Falak, Asfa; Irshad, Laila; Arooj, Momna; Jabeen, Saadia (Biological and Clinical Sciences Research Journal, 2025)
Acne vulgaris is a highly prevalent inflammatory dermatosis affecting adolescents and young adults, often requiring effective topical therapy for mild to moderate disease. Objective: To compare the effectiveness and safety of 5% dapsone gel versus 1% clindamycin gel in patients with mild to moderate acne vulgaris. Methods: A comparative cross-sectional study was conducted at the Department of Dermatology, CMH, Gujranwala, from August 2024 to January 2025, on 100 patients with mild to moderate acne vulgaris, equally divided into two groups of 50 each. Group A received 5% dapsone gel, and Group B received 1% clindamycin gel for 12 weeks. The study was carried out in a dermatology outpatient setting over three months. Acne severity was assessed at baseline and follow-up visits using standard acne grading and the Global Acne Grading System (GAGS). Data were analyzed using SPSS, applying appropriate comparative statistical tests, with a p-value <0.05 considered statistically significant. Results: Baseline acne severity was comparable between the two groups, with no statistically significant difference (p = 0.841). At week 12, complete acne clearance was achieved in 46% of patients in the dapsone group, compared with 18% in the clindamycin group, indicating a significant difference in favor of dapsone (p = 0.004). Mean GAGS scores at week 12 were significantly lower in Group A (6.5 ± 7.11) than in Group B (9.8 ± 8.44) (p = 0.024). Both treatments were well tolerated. Mild adverse effects included erythema (8% in both groups), irritation (8% in Group A vs 4% in Group B), and burning sensation (6% in Group A vs 4% in Group B). Conclusion: Topical 5% dapsone gel is more effective than 1% clindamycin gel in the treatment of mild to moderate acne vulgaris, providing faster and greater lesion clearance with minimal and comparable side effects. Larger multicenter studies are recommended to validate these findings.